Farmer-to-farmer technology diffusion and yield variation among adopters: the case of improved cowpea in northern Nigeria - Alene, A.; Manyong, Victor M. (Wiley, 2006)
This article examines the magnitude and sources of yield variation among adopters of improved cowpea varieties in northern Nigeria promoted through farmer-to-farmer diffusion. The results reveal important efficiency differences between the lead farmers who have contacts with breeders and the follower farmers who get technology and information from the lead farmers. Differential adoption of the package of seed, insecticide, fertilizer, and recommended cereal-cowpea cropping pattern provides much of the explanation for yield variation among adopters. The component often missing, and hence accounting for much of the yield variation, is the crop management technology relating to the cereal-cowpea cropping pattern. No efficiency variation is attributed to the source of technology and information, such as whether improved cowpea was obtained from breeders or lead farmers. Technology source has a rather indirect influence on efficiency through its effect on package adoption where breeders promote greater package adoption among the lead farmers than the lead farmers do among the follower farmers. Possible ways of disseminating crop management technological information through the farmer-to-farmer technology diffusion are recommended to better exploit the yield and profitability potentials of improved cowpea varieties in northern Nigeria.